Hybrid imaging and timing Ps laser excitation diagnostics for pulsed antihydrogen production - Caravita, Ruggero; Antonello, M.; Belov, A. S.; Bonomi, G.; Brusa, R. S.; Caccia, M.; Camper, A.; Castelli, F.; Comparat, D.; Consolati, G.; Demetrio, Andrea; Di Noto, L.; et al. (Acta physica Polonica, 2020)
In this work we present a hybrid detection method providing simultaneous imaging and timing information suitable for fully monitoring positronium (Ps) formation, its laser excitation, and its spatial propagation for the first trials of pulsed antihydrogen ((H) over bar) production through a charge-exchange reaction with trapped antiprotons ((p) over bar). This combined method, based on the synchronous acquisition of an EJ-200 scintillation detector and a microchannel plate (MCP) detector with a dual readout (phosphor screen image and electrical pick-up signal), allows all relevant events in the experiment to be accurately determined in time while allowing high resolution images of e(+) from Ps laser photodissociations to be acquired. The timing calibration process of the two detectors discussed in details as well as the future perspectives opened by this method.